Muscle injury and acupuncture (Advances in Exercise and Sports Physiology, 2010)
Muscle injuries frequently occur in sports, with muscle damage brought about by various causes. Numerous studies have reported that acupuncture increases blood flow, relieves pain and inflammation, strengthens muscles, and reduces abnormal muscle tone. In this review and study, we introduce some typical acupuncture techniques which can be used for treating muscle injury and describe each one's effect. The techniques we used in this study are Chishin, Jyakutaku, electroacupuncture and exercise acupuncture. It is important that when selecting a particular technique, that the time elapsed after injury be considered. As a result of investigating the effect of low-frequency electroacupuncture stimulation on the repair of damaged muscle, we found that Acupuncture stimulation accelerates the reduction in swelling and inhibits deutogenic necrosis of muscle and induces enlargement of regenerative muscle. Therefore, we suggest that acupuncture therapy has great effect on muscle injury, and helps in recovery from such injury.